DEXAMETHASONE DOWNREGULATES EXPRESSION OF TRIGGERING RECEPTOR EXPRESSED ON MYELOID CELLS (TREM)-1: EVIDENCE FOR A TNFα-RELATED EFFECT - Ira eMihailidou; Aimilia ePelekanou; Aikaterini ePistiki; Aikaterini eSpyridaki; Ira-Maria eTzepi; Georgia eDamoraki; Evangelos J Giamarellos-Bourboulis; Evangelos J Giamarellos-Bourboulis (Frontiers Media S.A., 2013)
Objectives To investigate the effect of dexamethasone on triggering receptor expressed on myeloid cells-1 (TREM-1).Methods Lethal infection was induced by Pseudomonas aeruginosa in 96 mice, both wild-type and TNF-/-; mice were pre-treated either with saline or with dexamethasone/hydrocortisone. TREM-1 on neutrophil membranes was measured after sacrifice. Monocytes of the U937 human cell line were challenged by LPS and heat-killed P.aeruginosa with the sequential addition of dexamethasone, hydrocortisone, TNFα and anti-TNF. Expression of TREM-1 and release of soluble TREM-1 (sTREM-1) in supernatants were measured.Results Pre-treatment with dexamethasone prolonged animal survival; this was not shown with hydrocortisone pre-treatment. Mice pre-treated with dexamethasone showed decreased expression of TREM-1 on neutrophils. LPS and P.aeruginosa induced the expression of TREM-1 and the release of sTREM-1 by U937 monocytes; that was decreased upon addition of dexamethasone but not of hydrocortisone. The effect of dexamethasone was enhanced upon addition of TNFα and lost in the presence of anti-TNF. The effect was also lost in TNF-/- mice. Gene expression of TREM-1 by U937 monocytes was decreased after treatment with dexamethasone.Conclusions TREM-1/sTREM-1 is a novel site of action of dexamethasone. This action is related with down-regulation of gene expression and is modulated by TNFα.